(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Local complications of intestinal stomas are a significant factor that determines the course of the early postoperative period and the effectiveness of rehabilitation. Their clinical structure is heterogeneous and depends on a variety of factors, which requires detailed analysis in order to develop differentiated approaches to patient management.